PENGEMBANGAN KARET DI INDONESIA ANTARA HARAPAN DAN KENYATAAN - Agus Santoso (Universitas Nasional, 2016)
There are four points in looking at the problems of rubber in Indonesia, among others: (1) low productivity, due to the lack of attention related parties in the field of research and development (R & D) rubber plant. (2) The revitalization program aimed at helping farmers access to funding, the fact that a lack of support from various parties so that the program runs half-hearted. The main obstacle faced by farmers for this is obvious because of the absence of a certificate of land owned by farmers for collateral to banks. The government's promise to help pass the certification of the National Program for Land (Prona) did not materialize. (3) The cause of the low productivity of crops including rubber farmers, for use seeds or seedlings are not superior. Besides farmers do not master the technique and procedure for the cultivation of rubber right and good. Moreover, in the control of wiretapping technology, the ability of farmers are also very minimal. (4) The last issue, where the location of smallholder plantations scattered in the scale area is relatively small with limited access, so the freight cost is high and less efficient. This can actually be overcome by expanding the planting area farmers planters people. The purpose of this paper would like to remind the observer of rubber, as a quick solution to overcome the problems of the rubber in Indonesia, although the problem has been widely discussed in various print media. But there is no harm in so far as it concerns the greater interest, especially farmers of rubber and rubber development issues in Indonesia. The method is descriptive qualitative analysis by tracing the ancient sources that have been made previously, in other words, peeling (criticize), compare (compare), summarizing (summarize), and collect (synthesize) a piece of literature. Later attempts to describe, record and interpret the condition now then do an evaluation.